2021
DOI: 10.1016/j.dld.2020.12.012
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in IBD: The experience of a single tertiary IBD center

Abstract: BACKGROUND Italy has been one of the most affected countries in the world by COVID-19. There has been increasing concern regarding the impact of COVID‐19 on patients with inflammatory bowel disease (IBD), particularly in patients treated with immunosuppressants or biologics. The aim of our study is to understand the incidence of COVID-19 in a large cohort of patients with IBD. Furthermore, we analyzed possible risk factors for infection and severity of COVID-19. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 25 publications
4
44
0
1
Order By: Relevance
“…Previous evidence regarding a higher risk of viral infections in IBD patients on thiopurine therapy [ 12 ], and a greater tissue concentration of angiotensin-converting enzyme 2 in patients with active intestinal inflammation [ 13 ], contributed to raising concerns regarding the threat of severe illness in IBD patients in the case of SARS-CoV-2 infection. Only in subsequent months did additional population studies show that patients affected by IBD had a risk of contracting coronavirus infection similar to that of the general population [ 14 , 15 ], regardless of the biological therapy [ 16 18 ]. However, it is still not known whether the outcomes of surgery performed on IBD patients during the period of highest pressure to the healthcare system were affected by the environment of a COVID-19-treatment hospital, and whether IBD surgery should be performed only in COVID-19-free facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence regarding a higher risk of viral infections in IBD patients on thiopurine therapy [ 12 ], and a greater tissue concentration of angiotensin-converting enzyme 2 in patients with active intestinal inflammation [ 13 ], contributed to raising concerns regarding the threat of severe illness in IBD patients in the case of SARS-CoV-2 infection. Only in subsequent months did additional population studies show that patients affected by IBD had a risk of contracting coronavirus infection similar to that of the general population [ 14 , 15 ], regardless of the biological therapy [ 16 18 ]. However, it is still not known whether the outcomes of surgery performed on IBD patients during the period of highest pressure to the healthcare system were affected by the environment of a COVID-19-treatment hospital, and whether IBD surgery should be performed only in COVID-19-free facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown thatpotential risk factors for SARS-CoV-2 infection include age, nutritional status, high comorbidities,andIBD activity [143] .Some studiesdemonstratedno association between IBD treatments and COVID-19 severe infection or mortality [144] , [145] . On the other hand, inthe SECURE-IBDclinical trial,theuse of systemic corticosteroids and sulfasalazine wasshown as serious risk factors for poor clinicaloutcomes in COVID-19 patients [146] , [147] .…”
Section: Vaccination In Immunocompromised Patientsmentioning
confidence: 99%
“…In a multicenter study from eight major gastrointestinal centers in Lombardy, Italy, IBD patients were not reported to have an increased risk of COVID-19 specific symptoms or more severe disease as compared with a control group of gastroenterology patients[ 65 ]. Another observational study confirmed that patients with IBD had a higher risk of COVID-19 incidence as compared to the general population and that tumor necrosis factor (TNF) antagonists may reduce the severity of COVID-19[ 66 ]. Singh et al [ 67 ] indicated no significant differences in the composite outcome of hospitalization or mortality between COVID-19 patients with IBD and those without.…”
Section: Ibd Patients With Sars-cov-2 Infectionmentioning
confidence: 99%